THE NEXUS OF ORGANIZATIONAL CULTURE AND AUTHORITY STYLE ON WORKER’S PERFORMANCE THROUGH WORK SATISFACTION - Basuki Basuki; Rahmi Widyanti; Nuning Kundayati; Aida Vitria (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
The current investigation set out to ascertain the following: the impact of organizational culture and authority style on work satisfaction and worker performance, as direct and indirect.This investigation used the SEM analysis and a quantitative approach to provide explanations. Number of 157 workers of PT PLN (Persero) SPI in the ATD Division made up the paper's population. The proportionate random sampling technique was used to carry out the sampling, resulting in 61 respondents.According to the paper's findings, from the six hypotheses had a direct impact in addition to having a positive and substantial effect. Nonetheless, the data processing findings revealed the following mediating effect: Worker performance was impacted by organizational culture through work happiness because worker performance was already directly affected by organizational culture even in the absence of work satisfaction. Work satisfaction impacts worker performance even in the absence of authority style.